Sirt1 and Nrf2: regulation of Leydig cell oxidant/antioxidant intracellular environment and steroid formation†. Issue 5 (7th August 2021) - Chung, Jin-Yong; Chen, Haolin; Zirkin, Barry
Abstract : Inhibition or knockout of Sirt1 or Nrf2 resulted in increased ROS and reduced cell testosterone production, and their activation protected or enhanced steroidogenic function, suggesting that Sirt1 and Nrf2 are involved in maintaining the Leydig cell oxidant/antioxidant environment and steroid production. Abstract: Previous studies reported that, with aging, Leydig cell intracellular antioxidants are reduced in concentration and intracellular ROS levels increase, suggesting that oxidant/antioxidant imbalance may contribute to the reduced testosterone production that characterizes the aging cells. As yet, little is known about how the Leydig cell oxidant/antioxidant environment is regulated. Sirt1, an enzyme that deacetylates transcription factors, and the transcription factor Nrf2, have been shown to be associated with cellular response to oxidative stress. We hypothesized that Sirt1 and/or Nrf2 might be involved in regulating the oxidant/antioxidant environment of Leydig cells, and therefore, the testosterone production. We found that Sirt1 and Nrf2 are present in the Leydig cells of Brown Norway rats, though reduced in aged cells. In MA-10 cells in which Sirt1 or Nrf2 were suppressed by nicotinamide (NAM) or ML385, respectively, or in which siRNAs were used for knockdown of Sirt1 or Nrf2, increased ROS levels and decreased progesterone production occurred. In rat Leydig cells, inhibition of Sirt1 by culturing the cells with NAM resulted in increased ROS and reduced testosterone production, and subsequent removal of NAM from the culture medium resulted in increased testosterone production. Activation of rat Leydig cells Sirt1 with honokiol or of Nrf2 with sulforaphane resulted in the maintenance of testosterone production despite the exposure of the cells to oxidizing agent. These results, taken together, suggest that Sirt1 and Nrf2 are involved in maintaining the Leydig cell oxidant/antioxidant environment, and thus in maintaining steroid production.